High efficient solar cells and modules based on diamond-like carbon film - multicrystalline Si structures - Klyui, N.I.; Korneta, O.B.; Kostylyov, V.P.; Litovchenko, V.G.; Makarov, A.V.; Dikusha, V.N.; Neselevska, L.V.; Gorbulik, V.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
In the work the results of investigations of developed and produced solar cells (SC) and modules (SM) characteristics are presented. It has been shown that due to application of hydrogen plasma treatment and deposition of diamond-like carbon films high efficient solar cells may be created. New constructions of solar modules having improved exploitation characteristics were proposed. The efficiency of the proposed scientific and design-technology approaches is illustrated by the example of the SC and SMs with the efficiency of 11-14 % and 11-12.5 %, correspondingly.